Das Literarische Moment der Wiederaufnahme im Pentateuch - Warning, Wilfried (Old Testament essays, 2023)
The resumptive repetition (Wiederaufnahme) is one of the literary devices used to shape the transmitted text in MT + Sam. To a certain degree, the first chapters of Genesis seem to be outlined by the relative particle אשר ("which") and the noun שמים ("heaven"). Part of the Abraham story is highlighted by the word שבע ("to swear"), גמל ("camel"), מכפלה ("Machpelah"), מערה ("cave"), הארץ את נתן ("to give the land") and the noun זרע ("seed, offspring"). Lastly, the Joseph story accentuates the terms כנען ארץ ("the land of Canaan"), צואר ("neck"), צמח ("to sprout"), שלום ("peace, well-being") and נכר ("to recognise"). The second part of this study will throw light on terminological patterns which underline different thematic and theological aspects in Exodus, Leviticus, Numbers and Deuteronomy. https://doi.org/10.17159/2312-3621/2023/v36n2a3